Reason in the theory of society : exploring the movement into and away from totalitarianism - Lim, Francine (2017)
How is it possible for a society, and with all its constituent members, willingly enter a state of subjugation? Notable endeavours to elucidate upon the totalitarian phenomenon include the advocate of civil disobedience and nonviolent resistance Étienne de La Boétie and one of the core members of the Frankfurt School of Critical Theory, Herbert Marcuse. By exploring both philosophers’ accounts for the degradation of liberty, this paper argues that reason is central to the onset of totalitarianism, and posits that critical theory presents a more justifiable account for the improvement of the human condition upon reacquisition of liberty.